INNOVATIVE APPROACHES TO THE PROCESS OF FORMATION OF CREATIVE PROFESSIONAL SKILLS OF FUTURE TEACHERS - Zakharchuk, T.V. (Pedagogy of Higher and Secondary Education, 2009)
The article covers the problem of forming of creative professional abilities of future teachers; opens up using the innovative methods of teaching, the pedagogical terms of forming of creative activity of future teacher are summarized.